A Comparison of the Effect of Interposed Abdominal Compression Cardiopulmonary Resuscitation and Standard Cardiopulmonary Resuscitation Methods on End‐tidal CO2 and the Return of Spontaneous Circulation Following Cardiac Arrest: A Clinical Trial. (20th March 2016) - Movahedi, Ali; Mirhafez, Seyed Reza; Behnam‐Voshani, Hamidreza; Reihani, Hamidreza; Kavosi, Ali; Ferns, Gordon A.; Malekzadeh, Javad
Abstract: Objectives: Sudden cardiac arrest is a major cause of death in the adult population of developed countries, with only 10%–15% of cardiopulmonary resuscitations (CPRs) being successful. We aimed to compare the effects of interposed abdominal compression CPR (IAC‐CPR) with standard CPR (STD‐CPR) methods on end‐tidal CO2 (ETCO2 ) and the return of spontaneous circulation (ROSC) following cardiac arrest in a hospital setting. Methods: After cardiac arrest was confirmed in a patient at Mashhad Ghaem Hospital, 80 cases were randomly assigned to one of the two methods of resuscitation, either IAC‐CPR or STD‐CPR, respectively. The inclusion criteria for the study were nontraumatic cardiac arrest, in patients between the age of 18 and 85 years, and the presence of endotracheal tube. Exclusion criteria were abdominal surgery in the past 2 weeks, active gastrointestinal bleeding, pulmonary embolism, and suspected pregnancy. Results: There was a significant difference between the two groups in ETCO2 (p < 0.003), but there was no significant difference as far as the ROSC (p > 0.50). Conclusion: The increase in the ETCO2 during IAC‐CPR is an indicator of the increase in cardiac output following the use of this method of CPR.